2019
DOI: 10.3390/w11081565
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Biochar from Various Waste Biomass as Biosorbent in Co(II) Removal Processes

Abstract: The removal of Co(II) ions from aqueous media was done using three types of biochars obtained from algae waste biomass, mustard waste biomass, and soy waste biomass. The biochar samples were obtained by pyrolysis of waste biomass resulted from biofules production, at relative low temperature (600–650 °C), and this procedure can be considered a suitable alternative to reduce the volume of such waste. FTIR spectra recorded for each type of biochar reveal the presence of several functional groups that can be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…5, the sorption appeared to be fast and after about 60 min for hornwort and 120 min for macroalga biochars, the equilibrium was achieved. A rapid sorption at the beginning of the process and rather short time to equilibrium was also observed in our recent work (about 80 min) in sorption of Cr(III) ions [21] and by Lucaci et al (about 60 min) in sorption of Co(II) ions [22]. This phenomenon was also widely observed in numerous researches dealing with metal sorption onto biochar or activated carbons and might be a result of rapid occupation of the external surface sorption sites, easily available over biochar surface.…”
Section: Sorption Properties Of Biocharssupporting
confidence: 87%
See 1 more Smart Citation
“…5, the sorption appeared to be fast and after about 60 min for hornwort and 120 min for macroalga biochars, the equilibrium was achieved. A rapid sorption at the beginning of the process and rather short time to equilibrium was also observed in our recent work (about 80 min) in sorption of Cr(III) ions [21] and by Lucaci et al (about 60 min) in sorption of Co(II) ions [22]. This phenomenon was also widely observed in numerous researches dealing with metal sorption onto biochar or activated carbons and might be a result of rapid occupation of the external surface sorption sites, easily available over biochar surface.…”
Section: Sorption Properties Of Biocharssupporting
confidence: 87%
“…In agreement with the principles of sustainable development, it is important to use waste as a raw material for other processes [20]. Biochars produced from aquatic biomass are mainly used for the removal of toxic metal ions from wastewater [21,22] or as a soil amendment [23,24]. Biochar from freshwater macroalga-Cladophora glomerata was examined as a sorbent of Cr(III) ions [21]; biochar from post-extraction of macroalga residues after oil extraction was used for sorption of Co(II) ions [22]; biochar from water hyacinth was investigated as a sorbent of Zn(II) and Cu(II) ions [25]; biochar from waste marine seaweeds-kelp and hijiki-was applied for sorption of Cd(II), Cu(II), and Zn(II) ions [26].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this advantage, the use of the activated carbon adsorption process for the removal of heavy metals has been limited as it requires high maintenance and operational costs [14]. In recent years, biochars, which can be produced at low cost, have attracted great attention as an alternative to activated carbon [15][16][17][18]. Biochar is an ecofriendly adsorbent produced using by-products of the agricultural industries and wastes from various crops, and is effective for removing heavy metals from wastewater [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Raw biochars have showed feasibility for adsorbent material to remove contaminants including heavy metals and organic pollutants [17,18,21,27,28]. However, the sorption capacities can be enhanced by treatment with acids, nanocomposites, and activation agents [17,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The Langmuir isotherm model assumes the number of active sites distributed homogeneously on the surface of the adsorbent followed by monolayer adsorption (physical adsorption) having high adsorptive power [37]. This suggested that the adsorption of NH 4 + takes place on the surface of the CB-GAC until a monolayer coverage was formed, after which the driving force of the sorption process decreases drastically [38]. The Q max calculated from the Langmuir model was 0.2821 mg/g.…”
Section: Characterization Of the Cb-gacmentioning
confidence: 99%